2023
DOI: 10.1021/jacs.3c07194
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Electronic Structure of Anion-Templated Silver Nanoclusters by Optical Absorption Spectroscopy and Theoretical Calculation

Yusuke Horita,
Sakiat Hossain,
Mai Ishimi
et al.

Abstract: Electronic structures of anion-templated silver nanoclusters (Ag NCs) are not well understood compared to conventional, template-free Ag NCs. In this study, we synthesized three new aniontemplated Ag NCs, namely [S@Ag 17 (S-4CBM) 15 (PPh 3 ) 5 ] 0 , [S@Ag 18 (S-4CBM) 16 (PPh 3 ) 8 ] 0 , and [Cl@Ag 18 (S-4CBM) 16 (PPh 3 ) 8 ][PPh 4 ], where S-4CBM = 4-chlorobenzene methanethiolate, and single-crystal X-ray crystallography revealed that they have S@Ag 6 , S@Ag 10 , and Cl@Ag 10 cores, respectively. Investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…Previous work demonstrated that [Ag 24 (CC t Bu) 20 (SiF 6 )] 2+ is colorless, implying that the absorption of the Ag 24 cluster is silent in the visible region . The pronounced absorption peak from 300 to 450 nm in the 99 TcO 4 – @Ag 24 crystal (Figures d and S3), consistent with the coloration effect of the [Ag 24 (CC t Bu) 20 ( 99 TcO 4 )] 3 + solution, suggested a distinct electron transition in 99 TcO 4 – @Ag 24 …”
supporting
confidence: 64%
See 1 more Smart Citation
“…Previous work demonstrated that [Ag 24 (CC t Bu) 20 (SiF 6 )] 2+ is colorless, implying that the absorption of the Ag 24 cluster is silent in the visible region . The pronounced absorption peak from 300 to 450 nm in the 99 TcO 4 – @Ag 24 crystal (Figures d and S3), consistent with the coloration effect of the [Ag 24 (CC t Bu) 20 ( 99 TcO 4 )] 3 + solution, suggested a distinct electron transition in 99 TcO 4 – @Ag 24 …”
supporting
confidence: 64%
“…Silver clusters are known to readily encapsulate anions within their cavities, as witnessed in diverse instances, such as [Ag 14 (CC t Bu) 12 X]­OH (X = Cl, Br), [Ag 19 (Bu t CC) 16 (CO 3 )]­BF 4 , and Ag 48 (CC t Bu) 20 (CrO 4 ) 7 . The cationic shell of the cluster is composed of multiple metal atoms that impart exotic physical–chemical properties. In this work, we found that 99 TcO 4 – @Ag 24 exhibits a broadband electronic absorption spectrum in the visible region, which is absent in other 99 TcO 4 – -containing counterparts, such as NaTcO 4 , KTcO 4 , etc. Theoretical investigations indicate that this absorption feature is governed by a distinct intermolecular charge transfer from Ag 24 electronic states to the lowest unoccupied molecular orbitals of 99 TcO 4 – , which is distinct from the well-known intramolecular electron transition within 99 TcO 4 – in other 99 TcO 4 – -bearing compounds.…”
mentioning
confidence: 70%
“…8 The structures of ligand-protected metal NCs can be solved by single crystal X-ray diffraction (XRD). 9,10 Following up on the breakthrough of Au 102 , an increasing number of gold 11–15 and silver NCs 16–19 have been isolated and structurally characterized. These NCs exhibit a characteristic structure comprising a metal core shielded by a monolayer of metal–ligand complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evolutionary algorithms offer a means to determine the necessary dimensions of precursor molecules for achieving a predetermined cage cavity size and associated properties . Therefore, the convergence of computational and experimental methodologies holds great promise for accelerating the discovery of new cage systems. , Particularly noteworthy is the application of rapid screening techniques of organic cages, thereby offering a consistent methodology to facilitate the development of materials with precisely tailored characteristics, , as well as the use of time-dependent DFT approaches to obtain detailed information about the electronic structure of metal clusters inside cages. , Here, we provide a detailed computational analysis of the recently described iminopyrrole cages, focusing on their intracavity dynamics, coordination plasticity, and other important properties, for which computational techniques can provide data complementary to the experimental data. Apart from the already mentioned plasticity of the system, we pay particular attention to the properties of potential mixed-valence Ag clusters, as this topic has recently attracted significant attention in the context of luminescence, fluorescence, chemical reactivity, , and other applications …”
Section: Introductionmentioning
confidence: 99%